Electron transport limitation in P3HT : CdSe nanorods hybrid solar cells - Lek, Jun Yan (2014)
Hybrid solar cells have the potential to be efficient solar-energy-harvesting devices that can combine the benefits of solution-processable organic materials and the extended absorption offered by inorganic materials. In this work, an understanding of the factors limiting the performance of hybrid solar cells is explored. Through photovoltaic-device characterization correlated with transient absorption spectroscopy measurements, it was found that the interfacial charge transfer between the organic (P3HT) and inorganic (CdSe nanorods) components is not the factor limiting the performance of these solar cells. The insulating original ligands retard the charge recombination between the charge-transfer states across the CdSe–P3HT interface, and this is actually beneficial for charge collection. These cells are, in fact, limited by the subsequent electron collection via CdSe nanoparticles to the electrodes. Hence, the design of a more continuous electron-transport pathway should greatly improve the performance of hybrid solar cells in the future.